The use of business intelligence systems in Australia - Dodson, G.; Arnott, D.; Pervan, Graham (Australasian Conference on Information Systems, 2008)
Business Intelligence (BI) systems are information systems that combine operational data, models, analytical tools and user interfaces to generate information to support business decision-making. BI is an important part of IT practice and is currently the highest technical priority for chief information officers. As there is to date no published academic research on the nature of BI practice we commenced an exploratory study of the area. A survey of business and IT professionals was used to test fourteen propositions about the nature of BI system adoption, development, use, and governance in Australia. This paper reports on the slice of results related to BI system use, including findings related to six propositions about the nature of BI system use. The survey highlights the critical role of BI in organizations, which justifies research effort into the area, as well as organizational spending on BI implementations.